Psychometric properties of the Work Well index: a short questionnaire for work-related stress - Mauss, Daniel; Li, Jian; Angerer, Peter (Stress and health, 2017)
The aim of this study was to test the psychometric properties of a short questionnaire for work-related stress entitled Work Well index (WWi) and its interaction with different variables of self-reported health. An online survey was conducted in a sample of 1,218 employees (51% female) in four countries of an international insurance company. Internal consistency reliability, factorial validity, convergent validity and criterion validity of the 10-item WWi were analyzed. Good internal consistency reliability of the WWi was obtained (Cronbach's α coefficient = 0.85). Confirmatory factor analysis showed a satisfactory model fit of the data (AGFI = 0.92). The WWi was highly correlated to conceptually close constructs such as demand-control, effort-reward imbalance and workplace social capital (p < 0.001). Moreover, the 10-item WWi was significantly (p < 0.001) associated with elevated risk of self-rated health, absenteeism, presenteeism and depression (odds ratio 1.63, 1.36, 2.08, 2.95, respectively). We conclude that this short questionnaire is a reliable and valid instrument measuring psychosocial stress at work.
Gesehen am 19.09.2018
Published online 24 February 2016